REKONSTRUKSI PENDIDIKAN KARAKTER DALAM RISĀLAH “ḤAYY BIN YAQẒĀN” KARYA IBN ṬUFAIL (Analisis Resepsi Sastra) - Latifi, Yulia Nasrul (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
In the middle of  seeking  the concept of character education recently, risālah “Ḥayy bin Yaqẓān” offers an  inclusive and holistic alternative  in  literature perspective. The risālah describes the life of  the main character, Ḥayy,  whose life is  full of knowledge, wisdom, and values from  chilhood to death. This research aims to show the reconstruction of character education pillars  and  the process of character  education building. The material object of this research is a risālah entitled  Ḥayy bin Yaqẓān written by Ibn Ṭufayl. The formal object is the reconstruction of character education. The theory  applied here is  a  reception  by Iser,  using a content analysis method. The results of this analysis reveals that the risālah consist of reconstruction of education pillars reflected on the character of Ḥayy. They are a willingness to learn, proactive and has a positive contribution  to his neigborhood,  emphaty and compassionate, cognitive  intelligence combined with a strength of soul, and be  faithful in God. The reconstruction of the process of character  education building is the internal factors (family), the external factors (millieu), and the principle of character education is a life long education.